IDIOM ‘SARU’ SEBAGAI REFLEKSI KONSEP PEMIKIRAN MASYARAKAT JEPANG TERHADAP MONYET - Devita Widyaningtyas Yogyanti (Universitas Diponegoro, 2018)
(Title: Idiom ‘Saru’ as a Reflection of Japanese People Thinking Concept Towards Monkey ). This research is an anthropological linguistic study that is conducted by examining the idioms that use the word